Climate change, transformative adaptation options, multiscale polycentric governance, and social welfare Towards an empirical evaluation in the context of Oum Er Rbia Basin, Morocco - Rathinasamy Maria Saleth; Amarasinghe, Upali; Amarnath, Giriraj; Ait El Mekki, Abdelkader; Brouziyne, Youssef (CGIAR System Organization, 2022)
The overall objective of the proposed research is to develop an empirically applicable methodology for capturing and evaluating the critical linkages between the relative success of transformative adaptation options and their relative effectiveness as determined by the underlying institutions and infrastructures at various scales and contexts. The methodology will cover both the individual and joint roles of institutional and infrastructural elements of multiscale and polycentric governance (MPG) structure in enhancing the effectiveness and climate resilience contributions of different transformative adaptation options.